Quality-in-use characteristics for clinical decision support system assessment. (August 2021) - Souza-Pereira, Leonice; Ouhbi, Sofia; Pombo, Nuno
Highlights: There are many advantages to using CDSSs, but there are still many challenges in their adoption. It is essential to ensure the quality of CDSS to mitigate its non-acceptance. Assessing or measuring the quality-in-use of a system can say much about the software quality, which affects the product and its users directly. We recommend satisfaction and efficiency as quality-in-use evaluation characteristics to better mitigate the gap in CDSSs usage. We presented a scenario to illustrate the assessment importance and improvement to the software product. Abstract: Background: Clinical decision support systems (CDSSs) are developed to support healthcare practitioners with decision-making about therapy and diagnosis' confirmation, among others. Although there are many advantages of using CDSSs, there are still many challenges in their adoption. Therefore, it is essential to ensure the quality of the system, so that it can be used confidently and securely. Objective: This study aims to propose a set of (sub)characteristics which should be considered in evaluating the quality-in-use of CDSSs, based on the ISO/IEC 25010 standard and on existing literature. Methods: We reviewed the existing literature on CDSS assessment and presented a list of quality characteristics evaluated. Results: Ten quality characteristics and 56 sub-characteristics were identified and selected from the literature, in which usability was evaluated the most. An example of a scenario has been presented to illustrate our assessment approach of satisfaction and efficiency as important quality-in-use characteristics to be applied in the evaluation of a CDSS. Conclusion: The proposed approach will contribute in bridging the gap between the quality of CDSSs and their adoption.